Septuagint, sages, and scripture : studies in honour of Johann Cook - Cook, Johann.; Gauthier, Randall X. (Vetus Testamentum, Supplements, 2016)
The studies collected in this volume were written in honour of Johann Cook, emeritus professor of the Department of Ancient Studies at Stellenbosch University. They cover a variety of subjects including the translation of Hebrew expressions into Greek, the reception of LXX texts in various contexts, topics related to wisdom and the LXX versions of sapiential literature, Ben Sira as a scribe of the Second Temple period, themes in the works of Philo and Josephus and the references to Sumkhos ben Joseph in rabbinic writings. The contributions therefore focus on the Septuagint, early Jewish sages and ancient scriptures. They present the results of original research, identify new lines and topics of inquiry and make novel contributions to existing insights.